Enzalutamide-Induced Upregulation of PCAT6 Promotes Prostate Cancer Neuroendocrine Differentiation by Regulating miR-326/HNRNPA2B1 Axis - Liu, Bo; Jiang, Hui-Yang; Yuan, Tao; Luo, Jie; Zhou, Wei-Dong; Jiang, Qi-Quan; Wu, Denglong (Frontiers in Oncology, 2021)
Our previous studies have demonstrated that Enzalutamide-induced upregulation of long-non coding RNA p21 (lncRNA-p21) facilitates prostate cancer (PCa) neuroendocrine differentiation (NED). Given the important role of lncRNAs in PCa pathogenesis and lots of lncRNAs are dys-regulated in neuroendocrine PCa (NEPC) patients, we next explored the biological function and underlying mechanism of lncRNA-PCAT6 (PCAT6) in mediating Enzalutamide-induced NED. The level of PCAT6 in Enzalutamide-treated PCa cells and NEPC samples were assessed using quantitative RT-PCR (qPCR). The effect of PCAT6 on PCa cell proliferation, invasion, and NED was evaluated through CCK-8, transwell, qPCR, western blot analysis, Xenograft mouse model, and in vivo lung metastasis model. We found that PCAT6 was highly expressed in NE-like cells (PC3, DU145, and NCI-H660) compared with androgen-sensitive LNCaP cells. PCAT6 was also highly expressed in NEPC tissues. Enzalutamide treatment resulted in a significant increase of PCAT6 level in dose- and time-dependent fashion. Functionally, PCAT6 overexpression promoted NED of C4-2 cells, as evidenced by an increased expression of NE markers (NSE, ChgA, and SYP), whereas PCAT6 knockdown in NCI-H661 cells repressed NED. Furthermore, PCAT6 overexpression promoted PCa cell proliferation and invasion in vitro and in vivo. Mechanistically, PCAT6 functioned as competing endogenous (ce) RNA via absorbing miR-326, thus resulting in a de-suppression of Hnrnpa2b1 target gene. The current results demonstrate that PCAT6 acted as a tumour activator in PCa progression by sponging miR-326 and increasing Hnrnpa2b1 expression and that the PCAT6/miR-326/Hnrnpa2b1 signaling might be a new therapeutic target for PCa.